Sensitivity analysis for performance and power density improvements in salient-pole synchronous generators - Wang, Yinli; Vakil, Gaurang; Nuzzo, Stefano; Degano, Michele; Galea, Michael; Gerada, C.; Zhang, He; Brown, Neil (2017)
Objective of this paper is to provide design recommendations to improve the performance and power density of a 400kVA salient-pole synchronous generator, without exceeding the limitations due to critical parameters such as total harmonic distortion of the no-load voltage. Preliminarily, a finite-element analysis of the considered machine is carried out, aiming at validating the inherent model against experiment measurements. An in-detailed sensitivity analysis of the machine’s design parameters that mostly affect the performance of the platform under investigation is performed. It has been found that the position and the shape of axial ventilation ducts, as well as the stator slot shape do not affect the electromagnetic performance in a significant way and it can be highly beneficial from a thermal point of view, resulting in reduced rotor temperatures. Additionally, the shape of the salient poles and the damper winding arrangement can produce positive effects on the general performance, particularly allowing for an improved voltage THD and power density of the machine being studied in this paper.